Occupational ergonomics : work related musculoskeletal disorders of the upper limb and back - Violante, Francesco; Kilbom, Åsa; Armstrong, Thomas J. (Taylor & Francis, 2000)
A collection of lectures from renowned international experts from the 1999 International Course for the Advanced Training in Occupational Health. Deals with work-related musculoskeletal disorders.